1954
DOI: 10.1111/j.1476-5381.1954.tb01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression of the Cough Reflex by Pentobarbitone and Some Opium Derivatives

Abstract: Experiments on the cough reflex (Larsell and Burget, 1924; Widdicombe, 1954a and b) have shown that two afferent nervous mechanisms are present. One has receptors lying in the trachea and is excited by mechanical stimuli, whereas the other extends throughout the tracheobronchial tree and is sensitive chiefly to irritant gases; the two types of cough stimulus give somewhat different motor responses. The central nervous pathways for coughing have not, however, been investigated, and little is known of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 6 publications
3
36
0
1
Order By: Relevance
“…In the cat, the antitussive potencies of codeine and dextromethorphan in the present study are similar to or greater than potencies reported by others (May & Widdicombe, 1954;Chau & Harris, 1980;Kase et al, 1983). In addition, in a model of fictive cough (Bolser, 1991) we have previously reported a potency of codeine (0.1 mg kg-', i.v.)…”
Section: Discussionsupporting
confidence: 67%
“…In the cat, the antitussive potencies of codeine and dextromethorphan in the present study are similar to or greater than potencies reported by others (May & Widdicombe, 1954;Chau & Harris, 1980;Kase et al, 1983). In addition, in a model of fictive cough (Bolser, 1991) we have previously reported a potency of codeine (0.1 mg kg-', i.v.)…”
Section: Discussionsupporting
confidence: 67%
“…As recently discussed by Bolser and colleagues (8,9), the evidence supporting the presence of a cough-gating mechanism derives in part from studies of the effects of antitussive drugs on the cough and breathing pattern (8,37). These authors propose that a cough-gating mechanism accounts for the fact that antitussive drugs do not suppress breathing at doses that inhibit cough, suggesting the presence of a neural component important for cough that does not participate in breathing pattern generation.…”
Section: Discussionmentioning
confidence: 94%
“…The evidence supporting the presence of a gating mechanism was obtained from studies of the effects of antitussive drugs on the cough and breathing patterns (May and Widdicombe, 1954;Bolser et al, 1999). This hypothesis accounts for the fact that antitussive drugs do not suppress breathing at doses that inhibit cough (May and Widdicombe, 1954;Bolser et al, 1999), suggesting the presence of an element important for cough that does not participate in the neurogenesis of breathing.…”
Section: The Gating Mechanismmentioning
confidence: 91%
“…This hypothesis accounts for the fact that antitussive drugs do not suppress breathing at doses that inhibit cough (May and Widdicombe, 1954;Bolser et al, 1999), suggesting the presence of an element important for cough that does not participate in the neurogenesis of breathing. Indeed, antitussive drugs do not inhibit tracheobronchial cough by a generalized suppression of the entire central cough pattern generator, rather they have very specific effects on various components of this system.…”
Section: The Gating Mechanismmentioning
confidence: 99%